EFFORTS TO COLLECT TAX WITH A PRIVATE LETTER IN INCREASING TAX REVENUE - Novi Aryani Retno Sari; Fitika Andraini (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
One source of state revenue that plays a very important role in increasing national development and aims to increase the prosperity and welfare of citizens is tax. Forced Letter (SP) is an order to pay tax debt and tax collection fees. A forced letter is issued if the tax bearer does not pay off the tax debt and a letter of reprimand or warning letter or other similar letter has been issued to him. This study aims to determine the efforts to collect taxes with forced letters in increasing tax revenues at KPP Pratama Pekalongan and to find out how effective tax collection by forced letters is in increasing tax revenues at KPP Pratama Pekalongan. This study uses a normative juridical approach, uses descriptive qualitative research specifications, and uses data collection techniques with primary and secondary data types.The results showed that efforts to collect taxes with forced letters in increasing tax revenue at KPP Pratama Pekalongan were carried out according to procedures, in the implementation of Tax Debt Collection with Forced Letters against Tax Underwriters at the Pekalongan Primary Tax Service Office encountered several obstacles, including because the tax bearer changed -change and not updated by the taxpayer and the tax collection department is less assertive in dealing with it taxpayers who do not want to pay on time. The effectiveness of tax collection by forced letter, based on tax collection by forced letter in 2020 tax revenue was 52,822,510,688, but the disbursement of tax arrears obtained was only 3,075,931,087 (6% contribution), while in 2021 tax revenue was 35,986,957,621 , but the disbursement of tax arrears amounted to 6,100,666,734 (17% contribution).